Manusia sebagai Peziarah Harapan: Titik Temu Pemikiran-pemikiran Filosofis Gabriel Marcel dan Ajaran Paus Fransiskus - Widyawan Louis, Aloysius (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
Pope Francis has declared 2025 as an Ordinary Jubilee Year with the theme Pilgrims of Hope (Peregrinantes in Spem). Amid a world grappling with various crises that threaten humanity and the natural environment, the Pope emphasizes the importance of hope, asserting that Christian hope never disappoints. This hope is not mere optimism or a denial of suffering and death but a virtue rooted in faith and realized through acts of love. In the tradition of Western philosophy, hope has also been a significant topic explored by Gabriel Marcel, a French philosopher, playwright, and music critic. This article seeks to uncover the strong correlation between Marcel’s philosophical reflections and Pope Francis’s magisterial teachings on hope. For Marcel, hope is fundamentally an inner drive that motivates and emboldens individuals to respond to the ontological exigencies of their existence, even while inhabiting a